2015
DOI: 10.1186/s12866-015-0405-9
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudomonas fluorescens type 6 secretion system is related to mucoidy, motility and bacterial competition

Abstract: BackgroundPseudomonas fluorescens strain MFE01 secretes in abundance two Hcp proteins (haemolysin co-regulated proteins) Hcp1 and Hcp2, characteristic of a functional type 6 secretion system. Phenotypic studies have shown that MFE01 has antibacterial activity against a wide range of competitor bacteria, including rhizobacteria and clinically relevant bacteria. Mutagenesis of the hcp2 gene abolishes or reduces, depending on the target strain, MFE01 antibacterial activity. Hcp1, encoded by hcp1, may also be invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 51 publications
(60 reference statements)
2
49
1
Order By: Relevance
“…The expression of hcp2 contributes to the killing activity of MFE01 against many Gram-negative bacteria, whereas hcp1 expression is involved in the immobilisation of prey cells. The competitor population was nevertheless reduced slightly by the double mutant, MFE01 Δhcp1Δhcp2 , suggesting the involvement of another factor in T6SS-mediated MFE01 killing activity [36]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The expression of hcp2 contributes to the killing activity of MFE01 against many Gram-negative bacteria, whereas hcp1 expression is involved in the immobilisation of prey cells. The competitor population was nevertheless reduced slightly by the double mutant, MFE01 Δhcp1Δhcp2 , suggesting the involvement of another factor in T6SS-mediated MFE01 killing activity [36]. …”
Section: Resultsmentioning
confidence: 99%
“…Gene knockout was performed, as previously described [36], with the suicide plasmid pAKE604 [37]. In-frame hcp3 disruption, due to the deletion of a central region of about 300 bp, was achieved by PCR with the muta1-hcp3-F and muta2-hcp3-R primers (product of about 650 bp) or the muta3-hcp3-F and muta4-hcp3-R primers (product of about 600 bp) (Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…100 However, in contrast to Caulobacter, for Pseudomonas the flagellum is of major importance for surface adhesion as the initial step of biofilm formation. 101 Moreover, Decoin et al 102 demonstrated an expressional link between flagellum compounds, such as flagellin, and the production of antimicrobial agents, and suggested that parallel motility and antibiotic production enhances competitiveness. The well-described antibiotic production by different members of Pseudomonas 103 may effectively suppress bacterial competitors, and might be another explanation for the decreased stability of the biofilm matrix.…”
Section: Role Of Microorganisms In Biofilm Matrixmentioning
confidence: 99%